1977
DOI: 10.1111/j.1651-2227.1977.tb07812.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Organic Acids in the Urine of the Newborn

Abstract: The urinary excretion of seven selected low molecular weight organic acids in normal neonates was measured by gas chromatography. First and third to fourth day of life excretion of the following compounds was significantly unchanged: 3-OH-butyric acid (less than 13 mumol/mmol creatinine), succinic acid (approx. 43 mumol/mmol creatinine), adipic acid (approx. 12 mumol/mmol creatinine), 2-OH-glutaric acid (approx. 23 mumol/mmol creatinine), 3-OH-3-Me-glutaric acid (approx. 25 mumol/mmol creatinine) and citric ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 14 publications
1
24
1
Order By: Relevance
“…There are no major discrepancies between the results of these studies and the present one, but comparisons are complicated by differences in sampling periods and analytical technique. The study of Gregersen et al, (1977) is very similar in design to ours, and the results also agree closely except for an unexplained higher urine concentration of citrate in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There are no major discrepancies between the results of these studies and the present one, but comparisons are complicated by differences in sampling periods and analytical technique. The study of Gregersen et al, (1977) is very similar in design to ours, and the results also agree closely except for an unexplained higher urine concentration of citrate in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Quantitative data on organic acids in urine from healthy newborns have recently been .published by other groups (Aksu et al, 1974;Bjorkman et al, 1976;Gregersen et al, 1977). There are no major discrepancies between the results of these studies and the present one, but comparisons are complicated by differences in sampling periods and analytical technique.…”
Section: Discussionmentioning
confidence: 50%
“…To investigate this hypothesis in hypoglycemic infants, we measured the urinary excretion of dicarboxylic acids in hypoglycemic and normoglycemic infants of group II. The val ues detected in the present study are slightly lower than those previously reported in neo nates [18,19]; the differences may be ex plained by the early timing in the present study and by the influence of feeding in the other reports. In the hypoglycemic infants, we did not observe an elevated urinary ex cretion of dicarboxylic acids in comparison to the normoglycemic infants.…”
Section: Discussioncontrasting
confidence: 56%
“…Lactic and 3-OH-butyric acids in d . , urine were determined by gas chromatography as tr~methylsilyl-derivatives after extraction with ethvlacetate (10). Measurement of glutaric and 3-OH-glutaric acidiin urine was performed by means of gas chromatography after ion exchange and trimethylsilylation, as described by Thompson and Markey (24).…”
Section: Methodsmentioning
confidence: 99%